Impact of institutional routine surveillance endomyocardial biopsy frequency in the first year on rejection and graft survival in pediatric heart transplantation. (18th May 2021) - Duong, Son Q.; Zhang, Yulin; Hall, Matt; Hollander, Seth A.; Thurm, Cary W.; Bernstein, Daniel; Feingold, Brian; Godown, Justin; Almond, Christopher
Abstract: Background: Routine surveillance biopsy (RSB) is performed to detect asymptomatic acute rejection (AR) after heart transplantation (HT). Variation in pediatric RSB across institutions is high. We examined center‐based variation in RSB and its relationship to graft loss, AR, coronary artery vasculopathy (CAV), and cost of care during the first year post‐HT. Methods: We linked the Pediatric Health Information System (PHIS) and Scientific Registry of Transplant Recipients (SRTR, 2002–2016), including all primary‐HT aged 0–21 years. We characterized centers by RSB frequency (defined as median biopsies performed among recipients aged ≥12 months without rejection in the first year). We adjusted for potential confounders and center effects with mixed‐effects regression analysis. Results: We analyzed 2867 patients at 29 centers. After adjusting for patient and center differences, increasing RSB frequency was associated with diagnosed AR (OR 1.15 p = 0.004), a trend toward treated AR (OR 1.09 p = 0.083), and higher hospital‐based cost (US390 315 vs. 313 248, p < 0.001) but no difference in graft survival (HR 1.00, p = 0.970) or CAV (SHR 1.04, p = 0.757) over median follow‐up 3.9 years. Center RSB‐frequency threshold of ≥2/year was associated with increased unadjusted rates of treated AR, but no association was found at thresholds greater than this. Conclusion: Center RSB frequency is positively associated with increased diagnosis of AR at 1 year post‐HT. Graft survival and CAV appear similar at medium‐term follow‐up. We speculate that higher frequency RSB centers may have increased detection of clinically less important AR, though further study of the relationship between center RSB frequency and differences in treated AR is necessary.